REGIONAL FEATURES OF FREQUENCY CHRONIC PERIODONTITIS, CYSTOGRANULOMA OR CYST OF PREMOLARS IN SOMATIC HEALTHY MEN BY THE DATA OF DENTAL EXAMINATION AND CT SCAN - Шінкарук-Диковицька, М.М. (World of Medicine and Biology, 2015)
Aim of our work - to set the frequency of chronic periodontitis, cysts of premolars or cystogranulomas of the upper and lower jaw in somatically healthy men from different regions of Ukraine according to the data of dental examination and cone-beam computed tomography.Materials and methodsAs a result of questioning more than 3,500 men aged 19 to 35 years selected 410 somatically healthy men in the third generation inhabitants of the respective environmentally friendly regions of Ukraine (North - Zhytomyr, Kyiv, Chernihiv and Sumy regions, South - Odessa, Nikolaev, Kherson, Zaporozhye region and Crimea, Central - Vinnytsia, Cherkasy, Kirovograd, Poltava and Dnipropetrovsk region; West - Volyn, Rivne, Lviv, Chernivtsi, Ternopil, Khmelnytsky, Transcarpathian and Ivano-Frankivsk region, East - Kharkiv, Donetsk and Luhansk region). All of them conducted: the study of dental status (full dental examination); cone-beam computed tomography (CT using Veraviewepocs 3D Morita) includes determining the status of the periapical tissues, crown and neck of the tooth (for hidden cavities); statistical analysis of the results conducted in the package "STATISTICA 6.1".Results. DiscussionsAccording to the data of CT on the upper jaw frequency of lesion premolars by chronic fibrous (on average from 1.4% in the south to 4.9% in the western region) and chronic granulomatous periodontitis (on average from 0.7% in the east to 6, 3% in the central region) has a higher value than the lower jaw (on average from 0% in the south and east to 1.5% in the northern region and from 0% in the northern and central to 1.4% in the southern region). Cystogranuloma and cyst of premolars on both upper and lower jaw in most regions is not defined. According to the data of dental examination found only on the upper jaw in less than 0.5% chronic fibrotic periodontitis in central and western regions.When comparing the frequency of periodontitis premolars between different regions statistically significant or trends to differences established only by the CT: on the upper jaw - higher values frequency of chronic granulomatous periodontitis 14 tooth in the central than in the southern and eastern regions and 24 tooth in the west than in the east and higher frequency value absence of periodontitis of 14 tooth in the east than in the central region; on the lower jaw - only larger frequency value cysts of 35 tooth in the west than in the central region.According to the data of dental examination set higher than the results of CT frequency value absence of periodontitis on the upper jaw for all teeth in most regions (most pronounced for 24 and 25 of teeth) and on the lower jaw only for 35th tooth in the western region. According to the data CT set higher than the results of dental examination value frequency of chronic granulomatous periodontitis of 14, 15 and 25 in the central and 24 tooth in the southern, central and western regions and frequency of chronic periodontitis fibrous of 14 in the central, 24 in the northern, central and western, and 25 tooth in the western region; and on the lower jaw - only larger frequency value cysts of 35 tooth in the western region.
Keywords: chronic periodontitis; cystogranuloma; cyst; premolars; somatically healthy men; different regions of Ukraine; dental examination; computed tomography